2018
DOI: 10.1002/adom.201701190
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Shot Laser Additive Manufacturing of High Fill‐Factor Microlens Arrays

Abstract: Various methods have been adopted for the high-FF fabrication of MLA. Hexagonal arrays with 100% FF have been demonstrated by self-assembly methods based on dewetting, [7] localized water condensation, [8] or surface wrinkling, [9] but these approaches typically lack control in the design and positioning of the microlenses. In contrast, photolithography techniques have become the gold standard for the production of customized high-FF MLA. [10][11][12][13] Even if unrivaled industrial upscaling is possible, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 36 publications
(41 reference statements)
0
31
0
Order By: Relevance
“…Thus, it has been proved that the technique is feasible for printing biomolecules like DNA and some proteins, and therefore for biosensor fabrication (Sections and ), and more recently it has been shown that FF‐LIFT is especially suited for printing living cells for tissue engineering applications (Section ). Another set of materials very attractive to be printed with the film‐free approach are optical grade adhesives, normally used in the fabrication of micro‐optical components …”
Section: Lift From Liquid Donor Filmsmentioning
confidence: 99%
“…Thus, it has been proved that the technique is feasible for printing biomolecules like DNA and some proteins, and therefore for biosensor fabrication (Sections and ), and more recently it has been shown that FF‐LIFT is especially suited for printing living cells for tissue engineering applications (Section ). Another set of materials very attractive to be printed with the film‐free approach are optical grade adhesives, normally used in the fabrication of micro‐optical components …”
Section: Lift From Liquid Donor Filmsmentioning
confidence: 99%
“…Typical requirements for the donor film are therefore a high absorption coefficient at the incident laser wavelength and high mechanical resistance upon bending to avoid internal rupture of the irradiated area during the deflection caused by expansion of the gas. [194,196,197] Microdisks of a positive photoresist (S1813) have been transferred onto flat and curved surfaces to form arrays of microlenses. [196] To this aim, the microdisks have been heated up to their glass transition temperature, which allow the formation of plano-convex microlenses through thermal reflow (Figure 12f-i).…”
Section: Other Solution-based and Hybrid Technologiesmentioning
confidence: 99%
“…[194,196,197] Microdisks of a positive photoresist (S1813) have been transferred onto flat and curved surfaces to form arrays of microlenses. [196] To this aim, the microdisks have been heated up to their glass transition temperature, which allow the formation of plano-convex microlenses through thermal reflow (Figure 12f-i). LIFT is highly versatile, allowing materials with diverse physicochemical properties to be assembled, and the geometries of the unitary building block to be varied during device building at variance with most AM methods, where the unitary building block is fixed by the laser spot size, the nozzle, or the printhead shape.…”
Section: Other Solution-based and Hybrid Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In LIFT, the receiver substrate does not need to be rigid so that flexible substrates such as polymers or paper can be employed as well. [ 25–32 ] In contrast to IJP, the absence of nozzle sets almost no restriction on the rheological properties of the ink. Several studies have proved the feasibility of LIFT for printing liquids with a wide range of viscosities (from 1 to 10 6 mPa s), [ 33–35 ] and suspensions containing large loading particles (up to 30 µm).…”
Section: Introductionmentioning
confidence: 99%